THE SIGNIFICANCE OF UNDERSTANDING ENGLISH GRAMMAR FOR EFFECTIVE COMMUNICATION - Hamdamova Dildora Elmurodovna (Web of Journals Publishing, 2025)
This article emphasizes the importance of mastering English grammar to achieve effective communication. It discusses how grammar provides the framework for constructing clear and coherent sentences, and how it helps speakers and writers convey their thoughts precisely. The article explores key aspects of grammar, including sentence structure, tenses, parts of speech, and punctuation, and how a solid understanding of these components can improve language proficiency.
Keywords: English grammar, Effective communication, Sentence structure, Verb tenses, Parts of speech, Punctuation, Clarity, Language proficiency, Grammar rules, Error correction, Language fluency, Writing skills.